Generations : academic feminists in dialogue - Kaplan, E. Ann; Looser, Devoney, 1967- (University of Minnesota Press, 1997)
Composed of essays from academic women at various professional stages-from established scholars to junior professors to graduate students-this collection illuminates the debates of feminist histories and future legacies, while analyzing the challenges of "passing the torch."
Comprised of original essays presented at various conferences held between 1993 and 1996.
Keywords: Feminism and education -- United States.; Feminist theory -- United States.; Universities and colleges -- United States -- Sociological aspects.; Women college students -- United States -- Social conditions.; Women college teachers -- United States -- Social conditions.; Féminisme et éducation -- États-Unis.; Féminisme -- Philosophie -- États-Unis.; Professeures (Enseignement supérieur) -- États-Unis -- Conditions sociales.; Étudiantes -- États-Unis -- Conditions sociales.; Universités -- États-Unis -- Aspect sociologique.; Théorie féministe -- États-Unis.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; Feminism and education; Feminist theory; Universities and colleges -- Sociological aspects; Women college students -- Social conditions; Women college teachers -- Social conditions; United States; Akademikerin; Feminismus; USA; Aufsatzsammlung